2014
DOI: 10.1002/bab.1284
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous efficient removal of high‐strength ammonia nitrogen and chemical oxygen demand from landfill leachate by using an extremely high ammonia nitrogen–resistant strain

Abstract: Bioaugmentation is a promising technology for pollutant elimination from stressed environments, and it would provide an efficient way to solve challenges in traditional biotreatment of wastewater with high strength of ammonia nitrogen (NH4(+)-N). A high NH4(+)-N-resistant bacteria strain, identified as Bacillus cereus (Jlu BC), was domesticated and isolated from the bacteria consortium in landfill leachate. Jlu BC could survive in 100 g/L NH4(+)-N environment, which indicated its extremely high NH4(+)-N tolera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Removal efficiency of NH 3 –N remarkably increased after the third day (47%) and improved until the last day of study. In a similar study, [ 6 ] reported that under optimum conditions (30 °C, pH 7.33, 4.14 days, and 170 rpm), 94.7% of NH 4 + –N was removed from landfill leachates that were treated with 3.5 mL of inoculated domesticated bacteria. The same trend was obtained for the sterilized samples (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Removal efficiency of NH 3 –N remarkably increased after the third day (47%) and improved until the last day of study. In a similar study, [ 6 ] reported that under optimum conditions (30 °C, pH 7.33, 4.14 days, and 170 rpm), 94.7% of NH 4 + –N was removed from landfill leachates that were treated with 3.5 mL of inoculated domesticated bacteria. The same trend was obtained for the sterilized samples (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A serious issue of landfill leachate is its high content of ammonia nitrogen (NH 3 –N), which prevents the activity and growth of microorganisms due to accelerate eutrophication and an increased dissolved oxygen reduction as well as toxic effects on aquatic organisms. Conventional treatment methods are challenging, especially for mature or old landfill leachate with NH 3 –N levels [ 6 8 ]. Organic matter in leachate is quantified by biochemical oxygen demand (BOD) and chemical oxygen demand (COD).…”
Section: Introductionmentioning
confidence: 99%
“…In the BTF process, several factors such as temperature, dissolved oxygen (DO), and reflux ratio (RR) can have impacts on treatment performance [23][24][25]. Therefore, the reliability of the system can be increased by a multistage BTF based on the A2O process (A2O-BTF).…”
Section: Introductionmentioning
confidence: 99%